Hypocaccus (Baeckmanniolus) laevis Thérond, 1963 is not synonymous with H. (B.) virescens Thérond, 1963 (Coleoptera: Histeridae: Saprininae) - Lackner, Tomáš (Zootaxa, 2013)
The synonymy of Hypocaccus (Baeckmanniolus) virescens Thérond, 1963 and Hypocaccus (Baeckmanniolus) laevis Thérond, 1963 is rejected following the examination of the type specimens of both species. Hypocaccus (Baeckmanniolus) laevis stat. restit. is reinstated as valid. The two species differ mainly in the dorsal sculpture, pronotal shape, shape of protibia as well as in other minor characters. Hypocaccus (B.) laevis is newly recorded from Kenya.